The Effect of Dosing of Goat Manure sludge and Rice Bran on Several Water Quality Parameters in Daphnia magna culture Media - Ahendra Massuhendri; Syafriadiman Syafriadiman; Niken Ayu Pamukas (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Green water is one of the growing media which can increase the growth of Daphnia magna. This study aims to determine the effect of green water on the abundance of D. magna. The method used was an experimental method with a completely randomized design (CRD) with 4 treatment levels and 3 repetitions. Treatment P0 = control, P1 = administration of green water at a dose of 7.5 ml/L, P2 = dose of 8.5 ml/L, P3 = dose of 9.5 ml/L. Green water is made with goat manure and bran. Then the two ingredients are mixed in a jar and water is added. Then let stand for 3-7 days and stirred every 2 times a day. The D. magna seeds used were 6 days old with a stocking density of 10 ind/L. The application of green water soaked in rice bran and goat manure had a significant effect on the abundance of D. magna. The best dose treatment was P3 which produced 2900 ind/l with the highest specific growth rate of 0.710746% with water quality that was still relatively good for the growth of D. magna.